PENGARUH PEMBERIAN ZAT PENGATUR TUMBUH Naftalene Acetic Acid (NAA) TERHADAP PERAKARAN SETEK TANAMAN SIRIH MERAH (Piper crocatum Ruiz & Pav) - Lismaini Lismaini (STIPER Dharma Wacana Metro, 2019)
This study aims to determine the effect of various concentration of NAA growt regulators on the root process of red betel and knowing the best NAA concentration in the roots of betel cuttings.The experimental design used in this study was a completely randomized design with one treatment namely the provision of NAA growt regulator with six levels of concentration namely without NAA (KD0), NAA 500 ppm (KD1), NAA 1000 ppm (KD2), NAA 1500 ppm (KD3), NAA 2000 ppm (KD4), NAA 2500 ppm(KD5) and repeated four times. The similarity of data variety was tested by Bartlett’s test and data addition was tested by Tukey test, the data were processed byanalysis of variance and the difference in the mean value was tested by the BNT test at the 5% level.Based on the result of research and observations that have been made to determine the effect of various concentration of NAA growt regulators on the root process of red betel and knowing the best NAA concentration in the roots of betel cuttings, so it can be concluded that giving NAA was significant for the number of roots, percentage of life and percentage of life and percentage of shoots. Meanwhile, giving NAA had no sifgnificant effect on the number of leaves, root lebght and shoot height. The best concentration are NAA 2000 ppm and 2500 ppm.